L’effort consacré à la recherche et au développement : un facteur explicatif de la structure et de l’évolution des exportations de pays industrialisés - Dulude, Louise (L'Actualité économique, 1978)
The aim of this study is to throw some new light on the empirical testing of the technological gap theory. The author studies the structure and growth of the exports of nine industrial countries in sixteen manufactured commodity groups during the 1963-1969 period. While it has been customary in the literature to link a country's export shares to the industries' R and D intensity, a distinction is made in this study between the R and D intensity and effort and it is concluded that a country's export structure and growth should be expressed as a function of its R and D relative effort in the different industries. Some empirical evidence of this new relationship is then given in static and dynamic settings.